Climate Change Impacts on Human Mobility and Migration: With reference to Anuradhapura and Puttalam Districts, Sri Lanka - Jayathunga, J.N.D. (Department of Geography, Faculty of Science, Masaryk University, Brno, Czech Republic., 2024)
Many nations, especially those with lower or middle incomes and economies that rely mostly on agriculture, are among the worst hit by climate change, according to the Global Climate Risk Index 2021. One of the most influential factors in human history is climate. It has primarily influenced all aspects of lifestyle, including economic, cultural, and social. People in ancient times adapted to their environment. Changes in the climate over the years have affected the economy, society, migration, and mobility. The objective of this study is to examine the influence of climate change on human lifestyles in terms of migration and mobility. This study combines quantitative and qualitative methods; secondary data is used to acquire information about climatic variability, while the latter approach uses Focus group discussions were conducted to study migration and mobility patterns and reasons. In the districts of Anuradhapura and Puttalam, hundred households from the agricultural sector were interviewed with a semi-structured questionnaire. This sample was chosen using a purposive and snow ball sampling. The mobility and migration trends in Sri Lanka are being affected by the irregular rainfall patterns, extreme weather events (droughts and floods) and rising temperature. Variability in the climate affects several aspects of agriculture, including the production of livestock, irrigation, agricultural farming, water management, and the economy overall. The households that make up the majority of the agricultural workers in Anuradhapura and Puttalam are rural residents who have suffered disproportionately from the effects of climate change. Agriculture in the Anuradhapura district is highly dependent on the seasonal rainfall due to the district's distinctive tank-based irrigated agriculture systems, particularly the small rainfed tanks found at the village level. Increased salinity levels, particularly as a result of the capillary rise of salt-rich groundwater produced by high air temperatures, are another consequence of drought that impacts Puttalam District. The effects of climate change on human migration and mobility have been identified in a variety of ways. Circular rural-urban movements are most prevalent in Colombo, Gampaha, Trincomalee, Kanthale, Kurunegala, and Galle whereas labour migration to the Kuwait, Italy, Korea, and Qatar is most common in Puttalam and Anuradhapura. Our research mainly aims to shed light on the connection between climate change and human migration as a result of failed farming methods. More effective reduction of climate change consequences can be achieved by actively encouraging ecologically friendly farming practices, which in turn will assist in accomplishing the Sustainable Development Goals (SDGs).
Keywords: Climate change; Human Mobility and Migration; Anuradhapura District; Puttalam District; Sri Lanka